The effects of solar radiation on heterothermy and metabolic thermogenesis capacity in the eastern rock elephant shrew Elephantulus myurus. - McKechnie, Andrew E. (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.